Head first HTML5 programming : building web apps with Javascript - Freeman, Eric, 1965- (Head first series., 2011)
HTML has been on a wild ride. Sure, HTML started as a mere markup language, but more recently HTML's put on some major muscle. Now we've got a language tuned for building web applications with Web storage, 2D drawing, offline support, sockets and threads, and more. And to speak this language you've got to go beyond HTML5 markup and into the world of the DOM, events, and JavaScript APIs. Now you probably already know all about HTML markup (otherwise known as structure) and you know all aboutCSS style (presentation), but what you've been missing is JavaScript (behavior).